Evaluation of the Use of Moist Potential Vorticity and Moist Potential Vorticity Vector in Describing Annual Cycles of Rainfall over Different Regions in Tanzania - Luhunga, Philbert M.; Djolov, George (Frontiers in Earth Science, 2017)
The economy of Tanzania heavily depends on agriculture sector which is primarily rain-fed. In this paper, we compute the moist potential vorticity (MPV) and evaluate its usefulness to describe annual cycles of rainfall. We also modify the convective vorticity vector ((CVV) ⃗) which was defined as the cross product of absolute vorticity and the gradient of equivalent potential temperature to moist potential vorticity vector ((MPVV) ⃗ ). This vector is calculated as a cross product of absolute vorticity and the gradient of moist air entropic potential temperature. The performance of (MPVV) ⃗ to describe the annual cycles of rainfall over different regions in Tanzania is analyzed. Twenty six (26) years (1976-2001) daily data of air temperature, specific humidity, zonal and meridional components of the wind at 850 and 600hPa from numerical output generated by the Rossby Center regional climate model version four (RCA4) are used for computation of MPV and (MPVV) ⃗ at 700hPa. The statistical relationship between (MPVV) ⃗ and MPV against observed rainfall data from 22 synoptic meteorological stations using Pearson correlation coefficient indicate that (MPVV) ⃗ bears strong and statistically significant correlation coefficient to rainfall than MPV suggesting its potential use as predictor of annual cycles of rainfall over different regions in Tanzania.